Putative role of HLA polymorphism among a Brazilian HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) population - Doris Schor; Luís Cristóvão Porto; Eric Henrique Roma; Julio Castro-Alves; Anna Paula Villela; Abelardo Q. C. Araújo; Maria Glória Bonecini-Almeida (Scientific Reports, 2023)
Abstract Around ten million people are infected with HTLV-1 worldwide, and 1–4% develop HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), characterized by an important degeneration of the spinal cord, which can lead to death. Distinct HLA alleles have been associated with either HAM/TSP susceptibility or protection. However, these HLA alleles set may change according to the population studied. Brazil is the second country in the number of HTLV-1-infected people and there are few reports addressing the HLA influence on HTLV-1 infection as well as on disease outcome. The objective of this study was to evaluate the influence of HLA alleles as a risk factor for HAM/TSP and the proviral load (PVL) levels, clinical progression, and death outcomes in an admixed Brazilian population. The HLA-A, -B, -C, and -DRB1 were genotyped in 375 unrelated HTLV-1-infected individuals divided into asymptomatic carriers (AC) (n = 165) and HAM/TSP (n = 210) in a longitudinal cohort from 8 to 22 years of follow-up. Because locus B deviated from Hardy–Weinberg Equilibrium for the study groups, the results represented for HLA-B alleles were inconclusive. The alleles HLA-A*68 and -C*07 were related to HAM/TSP risk in multivariate analysis. The alleles HLA-A*33, and -A*36 were associated with protection against disease progression in HAM/TSP patients, while -C*12, -C*14, and -DRB1*08 were associated with increased risk of death. In the AC group, the presence of, -C*06 and -DRB1*15 alleles influenced an increased PVL, in an adjusted linear regression model, while -A*30, -A*34, -C*06, -C*17 and -DRB1*09 alleles were associated with increased PVL in HAM/TSP group compared to HAM/TSP individuals not carrying these alleles. All these alleles were also related to increased PVL associated with clinical progression outcome. Increased PVL associated with the death outcome was linked to the presence of HLA-A*30. PVL has been associated with HLA, and several alleles were related in AC and HAM/TSP patients with or without interacting with clinical progression outcomes. Understanding the prognostic value of HLA in HAM/TSP pathogenesis can provide important biomarkers tools to improve clinical management and contribute to the discovery of new therapeutic interventions.